The influence of understanding Ing Ngarsa Sung Tuladha and understanding tax regulations on prospective taxpayers’ intention to comply - Wardani, Dewi Kusuma; Fajriani, Rizkina Ayu (Proceeding International Conference on Accounting and Finance, 2024)
This research aims to determine the influlence of ulnderstanding Ing Ngarsa Sulng Tulladha and Ulnderstanding of Tax Regullations on the Compliance Intentions of Prospective Taxpayers. The sample popullation for this research is all private stuldents in the Special Region of Yogyakarta. The sampling method ulsed by the aulthor is the convenience sampling method. This research ulsed qulantitative methods by distribulting qulestionnaires to 106 respondents. The resullts of this research show that the influlence of ulnderstanding Ing Ngarsa Sulng Tulladha has a positive effect and ulnderstanding tax regullations has no effect on the intention to comply with prospective taxpayers.